Prospek Ushatani pada Lahan Pesisir di Desa Pleret Kecamatan Panjatan, Kulon Progo - Ken Suratiyah; Tuti Wirdianingsih (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 1999)
Farm on seaboard land is another alternative besides farm in wet fields.